Fraction Board Design to Stimulate the Elementary School Students' Critical Thinking Ability Regarding Fraction - Puspita, Vivi; Zuwendi, Wulandari Juli; Alfiyandri; Dewi, Ika Parma (Postgraduate, University of Mataram, 2023)
This research is motivated by the limited use of mathematics learning media, especially in elementary schools, which can facilitate students' physical activity in building knowledge. This research aims to produce a product in the form of a fraction board that is feasible and has a good impact on the critical thinking skills of elementary school students. The type of research is RnD with the Pomp model. The test subjects in class IV SD N 31 Jati Tanah Tinggi consisted of 30 students. Data collection techniques use questionnaires, interviews and tests. The research results show that fraction board media is suitable for use with very valid criteria. Fraction board media is also easy to use and can train elementary school students' critical thinking skills.